Flicker transfer for three‐phase voltage source converter in distribution network. Issue 11 (1st May 2015) - Zhou, Niancheng; Pan, Shu; Wang, Qianggang
Abstract : Flicker transfer is significantly affected by the dynamic impedance of the three‐phase voltage source converter (VSC) in the distribution network. A methodology to determine the flicker transfer coefficient in a distribution system with a VSC is proposed. The formula of VSC dynamic impedance in the phase domain is derived based on the linearisation model of the VSC with the inner‐loop current control and outer‐loop power control as well as the phase‐locked loop block taken into consideration.